The Use Of Idioms In The Dark Knight Rises' Movie Script (Pragmatics Approach) - Listyantono, Rizki, Agus Wijayanto, Ph.D, Dr. Dwi Haryanti, M.Hum (2014)
This research focuses on analyzing the idioms in The Dark Knight Rises' movie script. The objectives are to describe the speech acts classifications, to identify the linguistics forms, and to describe the contextual meaning of the idioms in The Dark Knight Rises' movie script. This research applies descriptive qualitative method. The data are idioms found in the dialogue between characters in The Dark Knight Rises' movie script. The data source is the movie script entitled The Dark Knight Rises. The way to collect data is by using documentation method. The result of the research shows that, first, there are five classifications of speech acts of idiom in The Dark Knight Rises' movie script according to the context of the dialogue, representative, commissive, expressive, directive, and declaration. From 67 data, there are 38 idioms or 56.7% data belong to representatives, 1 idiom or 1.2% data belong to expressive, 4 idioms or 6.0% data belong to commissives, 16 idioms or 23.9% data belong to directives, and 8 idioms or 11.9% data belong to declarations. It means that the most dominant of the occurance is the idiom in representatives type as the one of the speech acts classifications. It also shows that most of the characters show and present about their opinion based on their representations related to some particular events in every dialogues in the movie script. Second, there are two main linguistics form in the idioms, they are sentence and phrase. In the form of sentence, there is 1 idiom or 1.2% data belong to the form of sentence. In the form of phrase, there are 81 idioms or 98.8% data (63 idioms or 94.0% data belong to phrasal verb, 1 idiom or 1.2% data belong to phrasal-prepositional verb, 0 idiom or 0% data belong to phrasal verb, 1 idiom or 1.2% belong to idiom with verb as keyword, 1 idiom or 1.2% belong to idiom with noun as keyword, 0 idiom or 0% data belong to idiom with adjective as keyword and 0 idiom or 0% data belong to idiomatic pairs). It means that most of the idioms in the movie script are in the form of phrase. The last, all of the idiom have the equivalence meaning related to the dictionary of the idiom and based on the context of the dialogue in The Dark Knight Rises' movie script.